EKSPLORASI FUNGI MIKORIZA ARBUSKULA (FMA) PADA RHIZOSFER POHON SAMAMA (Anthocephalus macrophyllus (Roxb.) Havil) - Lica, Evira Nurul Lica; Matinahoru, Johan M; Hadijah, Miranda H. (MAKILA, 2022)
ABSTRACT Samama (Anthocephalus macrophyllus) is a wood-producing tree with fast growth. Arbuscular mycorrhizal fungi status (AMF) can associate well with samama plants. This study aimed to determine the diversity of the genus and the number of spores of AMF in the rhizosphere of the samama plant, which has different soil types and environmental factors. The method used to obtain AMF spores was a wet filter pour and centrifugation technique at the center for plant seeds and plant protection for two months. Based on the research results in the village of Poka, it was found that there were four AMF genera with a total of 235 spores. Hatusua village found two genera of FMA with a count of 141 spores. In the village of Uraur, three genera of FMA were found with 479 spores. AMF spore production is influenced by the type of fungus and temperature, sunlight, soil pH, aeration, and water. The presence of mycorrhizae can increase soil fertility as a biological agent.